ChemInform Abstract: Carbothermal Reduction Synthesis Using CaCN2 as Calcium and Carbon Sources for CaAlSiN3:Eu2+ Phosphor and Their Luminescence Properties. Issue 35 (2nd September 2014) - Kim, Hyo Sung; Machida, Ken‐ichi; Horikawa, Takashi; Hanzawa, Hiromasa
Abstract High‐quality powders of the title phosphor are synthesized from mixtures of CaCN2, CaCo3:Eu3+, AlN, and Si3N4 (BN crucible, 0.1 MPa N2, 1600 °C, 5—7 h).